2020
DOI: 10.1016/j.heliyon.2020.e03274
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating depression with multimodal wristband-type wearable device: screening and assessing patient severity utilizing machine-learning

Abstract: We aimed to develop a machine learning algorithm to screen for depression and assess severity based on data from wearable devices. Methods: We used a wearable device that calculates steps, energy expenditure, body movement, sleep time, heart rate, skin temperature, and ultraviolet light exposure. Depressed patients and healthy volunteers wore the device continuously for the study period. The modalities were compared hourly between patients and healthy volunteers. XGBoost was used to build machine learning mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
61
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(65 citation statements)
references
References 56 publications
2
61
1
1
Order By: Relevance
“…Among the collected studies on wearable devices for patients with depression, two-thirds used actigraph units, while the rest used other devices such as a novel wearable device with three accelerometers (18); medically used wearable devices, such as a Parkinson's KinetiGraph (PKG) (23) and the E4 wristband (Empatica, Boston, MA, USA) (25); and commercial wearable devices not originally intended for medical use, such as the Fitbit Flex TM (Fitbit, Inc., San Francisco, CA, USA) (19), Apple watch (Apple Inc., Cupertino, CA, USA) (20), and Silmee TM W20 wristband (TDK Corporation, Tokyo, Japan) (22). Among the reviewed studies, no wearable devices were used for treatment.…”
Section: Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the collected studies on wearable devices for patients with depression, two-thirds used actigraph units, while the rest used other devices such as a novel wearable device with three accelerometers (18); medically used wearable devices, such as a Parkinson's KinetiGraph (PKG) (23) and the E4 wristband (Empatica, Boston, MA, USA) (25); and commercial wearable devices not originally intended for medical use, such as the Fitbit Flex TM (Fitbit, Inc., San Francisco, CA, USA) (19), Apple watch (Apple Inc., Cupertino, CA, USA) (20), and Silmee TM W20 wristband (TDK Corporation, Tokyo, Japan) (22). Among the reviewed studies, no wearable devices were used for treatment.…”
Section: Overviewmentioning
confidence: 99%
“…It contains a small touchscreen, which was used by Cormack et al (20) to offer tasks like cognitive and mood assessments to study participants. Finally, the Silmee TM W20 wristband was used previously (22) for unintended medical use and is equipped with a three-axis acceleration sensor, pulse sensor, ultraviolet sensor, and temperature sensor.…”
Section: Overviewmentioning
confidence: 99%
“…The attention-based deep learning model shows improvement of performance. Tazawa et al [49] develop a machine learning algorithm to screen for depression and assess its severity based on data from wearable devices. The use of machine learning and deep learning techniques for automation of sleep quality prediction has also been studied by some researchers.…”
Section: Related Workmentioning
confidence: 99%
“…Not only using single modality but combining multimodal data and with machine learning approach it may be more realistic to screen depression or to predict severity of depression. Utilizing wrist band-type wearable device that record three-axis acceleration, heart rate, body temperature, and ultraviolet light exposure, we have reported that it was possible to identify patients with depression with an accuracy of 0.76, and to predict depression severity with a 0.61 correlation coefficient with Hamilton Depression Rating Scale score ( 15 , 18 ).…”
Section: Introductionmentioning
confidence: 99%